Cholera Disease Control Strategies in Indonesia: A Review - Hikma Sri Nurwidiarni (Journal of Health Science and Pharmacy, 2025)
Background: Cholera is an acute diarrheal disease that continues to cause substantial morbidity and mortality worldwide. It is an intestinal infection caused by the bacterium Vibrio cholerae, transmitted primarily through the consumption of food or water contaminated with the pathogen, or through direct contact with carriers. In addition to its severe health implications, cholera is highly contagious and poses a significant threat to public health, particularly in areas with poor sanitation and limited access to clean water. Objective: This study aims to provide a comprehensive discussion of cholera, including its epidemiology, modes of transmission, clinical manifestations, diagnostic approaches, and strategies for control and prevention. Method: This research employed a literature review approach, synthesizing findings from published scholarly articles that address various aspects of cholera. The review was conducted by identifying, selecting, and summarizing relevant scientific publications to provide a consolidated understanding of the disease. Results: Control strategies incorporating vaccination, quarantine, and environmental sanitation measures have demonstrated effectiveness in reducing cholera incidence, thereby limiting disease transmission. The implementation of any single strategy among these three has been shown to sufficiently suppress infection rates. In contexts where financial constraints exist, quarantine of infected individuals has been identified as the primary and most cost-effective control measure. Conclusion: Effective cholera control requires a multifaceted approach integrating improved sanitation, targeted quarantine for individuals presenting with severe symptoms, public health education for at-risk populations, and water treatment interventions such as chlorination. Collaborative engagement with international health organizations, such as Nigeria’s participation in the World Health Organization (WHO), can strengthen national capacity to address persistent health challenges. Optimal prevention and control strategies should be adapted to local epidemiological contexts to ensure sustainability and impact. Keywords: Cholera, Control Strategies, Public Health, Indonesia